Commercial Crime Control and the Electronic Monitoring of Offenders in England and Wales - Paterson, Craig (Social justice, 2007)
A study was conducted to examine commercial crime control and the electronic monitoring (EM) of offenders in Great Britain. Data were obtained from British government documents concerning EM and from a review of the criminal justice literature. Findings revealed that the growth of EM has taken place in Britain despite a lack of conclusive evidence that it either protects the public or reduces rates of re-offending; so far, consultation and “evidence” have legitimized rather than informed policy, which helps to explain the diverse use of EM and the lack of a coherent policy steering its use. Findings also revealed that questions regarding the future role of the private sector in the criminal justice system have yet to be answered. Findings are discussed in detail.